A generic buffer occupancy expression for stop-and-wait hybrid automatic repeat request protocol over unstable channels - Darabkh, Khalid A.; Ibeid, Huda; Jafar, Iyad F.; Al-Zubi, Raed T. (Telecommunication systems, 2016)
Recently, there has been a rapid progress in the field of wireless networks and mobile communications which makes the constraints on the used links clearly unconcealed. Wireless links are characterized by limited bandwidth and high latencies. Moreover, the bit-error-rate (BER) is very high in such environments for various reasons out of which weather conditions, cross-link interference, and mobility. High BER causes corruption in the data being transmitted over these channels. Therefore, convolutional encoding has been originated to be a professional means of communication over noisy environments. Sequential decoding, a category of convolutional codes, represents an efficient error detection and correction mechanism which attracts the attention for most of current researchers as for having a complexity that is dependent to the channel condition. In this paper, we propose a new queuing study over networking systems that make use of sequential decoders. Hence, the adopted flow and error control refer to stop-and-wait hybrid automatic repeat request. However, our queuing study is a novel extension to our prior work in which the lowest decoding complexity was fixed and did not account for the channel state. In other words, our proposed closed-form expression of the average buffer occupancy is totally generic and parameterized by not only channel condition and packet incoming rate, but also those that are automatically adapted to the channel conditions which include lower and upper bound decoding limits.